ENHANCING TEACHER COMPETENCE THROUGH KKG PAI'S ROLE: A CASE STUDY IN LUMBANG, PROBOLINGGO - Nazahah Ulin Nuha; Maulid Agustin; Robiatul Adawiyah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2025)
The role of the Islamic education teacher work group is very important in building the quality of teacher competence. The purpose of this research is to find out the work program of the Islamic Education Teacher Work Group (KKG) in building the quality of Islamic Education teacher competence, to know the strategies of the Islamic Education KKG in building the quality of teacher competence, and to know the contribution of KKG in building the quality of Islamic Education teacher competence in Lumbang District, Probolinggo Regency. This research uses a descriptive qualitative approach. Data collection methods consist of observation and interviews with teachers who are members of the KKG. The informants are members of KKG in Lumbang District, Probolinggo Regency. The existence of a Work Program organized by the Islamic Education KKG means the competence possessed by Islamic Education teachers in Lumbang District, Probolinggo Regency. The results of this study indicate that the development of pedagogical competence of Islamic Education teachers in Lumbang District, Probolinggo Regency in terms of: 1) Mastering learning theory and principle, teachers develop various teaching techniques, motivate students with responsive and reciprocal stimulus. 2) Curriculum development, teachers are able to formulate, organize, design lesson planning programs, use media and learning models by using information and communication technology media. 3) In the development of educational activities, teachers have been able to pay attention to the level of needs, environment, opportunities, intellectuality, spirituality, psychology, and emotional aspects of students by applying skills.